Pendekatan Metode Bermain dalam Meningkatkan Kecerdasan Kognitif Anak Usia Dini di PAUD Arastamar Kids - Zega, Mei Mesrawati; Tapilaha, Sandra Rosiana (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
This research aims to improve the cognitive intelligence of early childhood at Arastamar Kids PAUD using a play method approach. Considering that children tend to spend much time playing from an early age and their cognitive abilities are still weak, it is important to apply the right approach to educating them. Early childhood education plays an important role in children’s mental, emotional and social development, especially in the 0-8-year phase. The play method was chosen as the main strategy in learning because it is considered capable of providing a fun and effective experience for children’s intellectual development. This service program is carried out at PAUD Arastamar Kids in Pekanbaru by involving teachers and students in a series of play activities designed to stimulate children’s critical thinking and problem-solving skills. This activity is held every Monday to Saturday from 08.00 to 11.00 WIB, with play sessions held before and after formal learning. The evaluation results show a significant increase in students’ cognitive intelligence, demonstrated through increased academic grades and ability to complete creative tasks. The play method approach has proven to be effective in creating a fun and interactive learning environment, as well as contributing positively to children’s cognitive development.